An Apriori-based Data Analysis on Suspicious Network Event Recognition - Jian, Z. (Institute of Electrical and Electronics Engineers Inc., 2019)
Apriori-based rule generators, which are powered by the DIS-Apriori algorithm and the NIS-Apriori algorithm, are applied to analyze the data sets available in the IEEE BigData 2019 Cup: Suspicious Network Event Recognition. Then, each missing value in the test data set is decided by using the obtained rules. The advantage of our rule-based model is that the obtained rules are very easy to understand in comparison with other 'black-box' machine learning models. Furthermore, two algorithms preserve the logical property 'completeness,' so they generate rules without excess and deficiency. In evaluation, the AUC measure seems unfavorable to our model, so we employed 3-fold cross-validation for the training data set, and we obtained a 94 mean score. This result ensures the validity of our model. We report several meaningful results in this experiment, as well as the estimation of missing values. Â© 2019 IEEE.